Antifungal compounds with anticancer potential from Trichoderma sp. P8BDA1F1, an endophytic fungus from Begonia venosa - Grigoletto, Diana F.; Trivella, Daniela B. B.; Tempone, André G.; Rodrigues, André [UNESP]; Correia, Ana Maria L. [UNESP]; Lira, Simone P. (Springer Nature, 2020)
Fungi in the genus Trichoderma are notorious producers of secondary metabolites with diverse applications, such as antibacterial, antifungal, and plant growth-promoting properties. Peptaibols are linear peptides produced by such fungi, with more than 440 compounds described to date, including tricholongins, longibrachins, trichobrachins, and trichovirins. Peptaibols are synthesized by non-ribosomal peptide synthetases and they have several biological activities. Our research group isolated four peptaibols (6DP2, 6DP3, 6DP4, and 6DP5) with antifungal activity against the plant pathogen Colletotrichum gloeosporioides and the proteasome (a cancer chemotherapy target) from Trichoderma sp. P8BDA1F1, an endophytic fungus from Begonia venosa. The ethyl acetate extract of this endophyte showed activity of 6.01% and 75% against C. gloeosporioides and the proteasome, respectively. The isolated compounds were identified by MS/MS and compared to literature data, suggesting the presence of trilongins BI, BII, BIII, and BIV, which are peptaibols containing 20 amino acid residues. The minimum inhibitory concentration against C. gloeosporioides was 40 μM for trilongin BI, 320 μM for trilongin BII, 160 μM for trilongin BIII, and 310 μM for trilongin BIV. BI–BIV trilongins inhibited proteasome ChTL activity, with IC50 values of 6.5 ± 2.7; 4.7 ± 1.8; 6.3 ± 2.2; and 2.7 ± 0.5 μM, respectively. The compounds were tested ex vivo against the intracellular amastigotes of Leishmania (L.) infantum but showed no selectivity. It is the first report of trilongins BI–BIV with antifungal activity against C. gloeosporioides and the proteasome target.
Keywords: Alcatrazes Island; Colletotrichum gloeosporioides; Peptaibiotics; Peptaibols; Proteasome